Martha: the cookbook ebook 100 favorite recipes, with lessons and stories from my kitchen. - Stewart, Martha (2024)
#1 NEW YORK TIMES BESTSELLER • Martha Stewart celebrates her landmark 100th book with an intimate collection of 100 treasured recipes, along with stunning photos from her personal archives and the stories behind them. A must for anyone who has ever been inspired by the one and only Martha. Join Martha in the kitchen as she shares favorite recipes and invaluable tips. Learn how to cook her mother’s humble Potato Pierogi , her decadent Gougères, a comforting Apple Brioche Bread Pudding , and the famous Paella she makes for the luckiest friends who visit her in summer. You’ll find something to satisfy everyone’s taste, whether it’s a simple meal you make for yourself, a weeknight family dinner, or a special celebration, recipes range from breakfast & brunch to soups & salads, hors d'oeuvres, cocktails, dinner, and of course dessert. Like a scrapbook of Martha’s life in cookbook form, this is the ultimate collection for devotees as well as newer fans who want to become more confident in the kitchen and do what Martha does best: Start with the basics and elevate them. From timeless classics to contemporary delights, these recipes reflect storied moments from her legendary, trailblazing career.